Analysis of the Socio-Economic Potential of the Community in the Mulawarman Museum Area - Wulandari, Mesy Ayu; Reza, Reza; Rahayu, Vitria Puri (Jurnal Ilmiah Wahana Pendidikan, 2024)
The low number of visits to the Mulawarman Museum area reduces buying and selling activities, which can hamper local economic growth. The research aims to determine the local socio-economic potential in the Mulawarman Museum area. This type of research was carried out using descriptive research with a qualitative approach, data collection was carried out by conducting interviews with 15 business actors and 3 people in the Mulawarman Museum area. Based on the research results, it shows that there is significant economic potential in the area. Effective sales strategies, such as friendly service, discounts, and product stock additions, have been proven to be able to attract more buyers and increase revenue. Apart from that, social interaction between business actors and customers plays an important role in increasing satisfaction and building better long-term relationships, so this area has the potential for further development. Optimal utilization of social and economic potential in the Mulawarman Museum area can create a positive impact on regional development and improve the welfare of local communities.